Comparing the urban impacts of the FIFA World Cup and Olympic Games from 2010 to 2016 - Müller, M.; Gaffney, C. (Journal of Sport and Social Issues, 2018)
At a cost of often more than US$10 billion, mega-events such as the Olympic Games and the FIFA Men`s World Cup are the single most transformative urban project in many host cities for decades. This article develops an analytical matrix for comparing the impacts of these events on cities and proposes a case survey method to apply this matrix to six recent sports mega-events: the Olympic Games in Vancouver, London, Sochi, and Rio de Janeiro and the FIFA Men`s World Cups in South Africa and Brazil. We find that for the events in our sample, it is not so much the event itself, but the political and economic contexts that most influence impacts. Cities in democracies with more market-led economies experienced fewer adverse impacts and were better able to use the event for urban development than those in less democratic countries with more state-led economies. None of the cities, however, was able to avoid negative impacts.